New focal mechanism solutions for Venezuela and neighbouring areas 2005-2008: importance of the National Seismological Network”™s density and distribution - Palma, Miguel; Audemard, Franck; Romero, Gloria (Rev. Téc. Fac. Ing. Univ. Zulia, 2012)
Â The purpose of this work is to show 66 new focal mechanism solutions for some seismic events which have occurred in Venezuela and neighbouring areas between October 2005 and December 2008. All this solutions were obtained through P-wave first motion polarity registered by the Venezuelan Seismological Network operated by FUNVISIS, and additional information provided by INGEOMINAS (Colombia) and the University of the West Indies (Trinidad and Tobago). All these focal mechanism solutions increase and reinforce our knowledge in the Venezuela regional/local tectonics as well as indicating the scope and potential of the Venezuelan Seismological Network which has been upgraded (enlarged and modernized) since 1998, being fully operative in 2002.